FEMINISM IN THE WORK OF CHRISTIAN WOMEN POETS - Sumita Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The world of the English novel received a huge boost from the contributions of Indian female authors. The Indian novel has significantly developed in terms of both its breadth of content and its level of maturity. It is not difficult to trace the gradual growth of the Indian novel's development from the imitative phase, through the rational stage, the psychological stage, and finally into the investigative phase. These evident tendencies emerge in the novel's evolution over time. The decade of the 1980s holds a special place in the history of the expansion and development of the Indian English novel. During this time period, the first novels of some extremely gifted female authors were released to the public. There are also some elderly masters whose works demonstrate that their creative skills remained intact throughout their careers. In the 1980s, Indian women authors were recognized with medals and accolades that were without comparison, not just in India but also in other countries. The works of these Indian women authors, much like the works of female novelists writing in the third generation, speak eloquently of their uniqueness and an ingenuity that is unmatched.